Telaah Normatif Tujuan Pendidikan Agama Islam Berdasarkan Pemikiran Ibnu Khaldun - Hasyim Azhari Siregar; Muhammad Yunan Harahap; Charles Rangkuti (Medan Resource Center, 2026)
This study aims to analyze the objectives of Islamic Religious Education based on the thoughts of Abdurrahman Ibnu Khaldun, with a focus on its relevance to contemporary education. This research employs a qualitative approach using library research methods, which involves collecting data through various literatures related to Ibnu Khaldun's views on education, particularly those outlined in his work Muqaddimah. The primary data sources include books, academic articles, and other relevant sources related to this topic. Data collection is carried out through document analysis, examining the content of texts relevant to the objectives of Islamic Religious Education according to Ibnu Khaldun. The results show that Ibnu Khaldun's concept of education encompasses not only intellectual aspects but also the formation of character, morals, and moral understanding. He emphasizes the importance of balancing worldly and spiritual happiness in education, while integrating the development of faith and moral values as an essential part of learning. His ideas are relevant for forming a comprehensive, value-based framework for Islamic Religious Education. The implication of this research is the need to realign the objectives of Islamic Religious Education with the demands of the times, so that religious education can shape individuals who are intellectually capable, morally upright, and prepared to face future social and spiritual challenges.